« Né pour être esclave »: migration transnationale des bergers d'une comunidad andine - Nuijten, Monique; Lorenzo, David; Tanguay, Michel (Anthropologica, 2022)
This article discusses the transnational migration of Peruvian shepherds from the central Andes to ranches on the west coast of the United States. On the basis of ethnographic research in the comunidad campesina (peasant community) of Usibamba, we delve into the consequences of this long-term migration for the families left behind, especially the wives, and for the operation of the comunidad campesina. We analyze the paradoxical ways in which the exodus of shepherds leads to a questioning of the control of the comunidad over its members but at the same time strengthens its disciplinary regime. Empirical examples show how the role of women in the comunidad is shifting as a result of this male exodus.